2021
DOI: 10.1177/2165079920975388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of California Safe Patient Handling Legislation: Health Care Workers’ Perspectives

Abstract: Background: Musculoskeletal injuries from patient handling are significant problems among health care workers. In California, legislation requiring hospitals to implement safe patient handling (SPH) programs was enacted in 2011. This qualitative study explored workers’ experiences and perceptions about the law, their hospital’s SPH policies and programs, patient handling practices, and work environment. Methods: Three focus groups were conducted with 21 participants (19 nurses and 2 patient handling specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…One possible reason for these findings may have to do with greater use of equipment. Specifically, a qualitative study reported that some nurses expressed concerns about shoulder and neck injuries related to more frequent use of ceiling lifts 36 . In the Minnesota study, 34 the PHI indemnity claims rate for shoulder injuries showed an initial increase during the first 3 years of postlegislation periods and then showed gradual decreases, which were statistically significant; however, the study observed little change for the PHI claim rate for neck injuries.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One possible reason for these findings may have to do with greater use of equipment. Specifically, a qualitative study reported that some nurses expressed concerns about shoulder and neck injuries related to more frequent use of ceiling lifts 36 . In the Minnesota study, 34 the PHI indemnity claims rate for shoulder injuries showed an initial increase during the first 3 years of postlegislation periods and then showed gradual decreases, which were statistically significant; however, the study observed little change for the PHI claim rate for neck injuries.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, a qualitative study reported that some nurses expressed concerns about shoulder and neck injuries related to more frequent use of ceiling lifts. 36 In the Minnesota study, 34 the PHI indemnity claims rate for shoulder injuries showed an initial increase during the first 3 years of postlegislation periods and then showed gradual decreases, which were statistically significant; however, the study observed little change for the PHI claim rate for neck injuries. In interpreting the study findings, our case definitions and limitations in case identification methods from the WC data system and data quality issues should be considered.…”
Section: Changes Of Msd and Msd-phi Claims By Injury Characteristicsmentioning
confidence: 93%
“…Large patient ratios have notable negative impacts on nurses and patients. This is often due to inadequate staffing (Cengiz et al, 2021 ; Chua et al, 2019 ; Lee et al, 2021 ; Tamata et al, 2021 ), but also an overall higher number of patients admitted and lack of coverage of sick calls or annual leave (Tamata et al, 2021 ). Contributing to the large patient ratios is the current coronavirus pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts have been made to reduce injuries among healthcare workers and some progress has been made. OSHA as well as the American Nurses Association (ANA) has campaigned for a safer work environment in hospitals through safe patient handling programs (American Nurses Association [ANA], 2021; Lee et al, 2021). The ANA has published the second edition of Interprofessional National Standards for safe patient handling and mobility signaling continued commitment to preventing injuries in the workplace (2021).…”
Section: Introductionmentioning
confidence: 99%
“…The average grip strength in the U.S. population has decreased dramatically since the 1980s normative data (Vanderbilt, 2017). Grip strength is an effective indicator of present and future health status (Bohannon, 2015(Bohannon, , 2019Carney & Benzeval, 2018;Lee et al, 2021;Leong et al, 2015;Wang et al, 2018). Decreased grip strength reflects lower overall strength and upper limb function, and is associated with increased risk for musculoskeletal injury, cardiac events, and other health problems (Bohannon, 2019).…”
Section: Introductionmentioning
confidence: 99%